Efficacy of the New Double-Layer Stent for Unresectable Distal Malignant Biliary Obstruction: A Single-Center Retrospective Study - Ito, Ken (Hindawi Publishing Corporation, 2012)
Background and Aims. For distal malignant biliary obstruction in cases with short life expectancy, occlusion of plastic stents (PSs) does not usually occur before death, and the application of such a procedure is considered adequate from the viewpoint of cost-effectiveness. Methods and Setting. A new commercially available DLS with side holes, a conventional DLS, and, uncovered self-expanding metal stents (SEMSs) were retrospectively evaluated in patients with jaundice due to unresectable distal malignant biliary obstruction. Results. A total of 64 patients received endoscopic biliary stenting (23 patients with the new DLS, 24 patients with conventional DLS, and 17 patients with uncovered SEMS) from December 2002 to August 2009. Median patency time was found to be 198 days for the new DLS group and 99 days for the conventional DLS group, revealing a significant difference between devices. There was, however, no significant difference in median patency time between the new DLS and the uncovered SEMS (198 days versus 344 days). Conclusion. The new DLS is efficient and safe and may be considered the first choice for unresectable distal malignant obstruction in cases with short life expectancy.